Short Communication: In vitro antibacterial activity of essential oils from twelve aromatic plants from East Kalimantan, Indonesia - HARLINDA KUSPRADINI; AGMI SINTA PUTRI; SAAT EGRA; YANTI .YANTI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Kuspradini H, Putri AS, Egra S, Yanti. 2019. Short Communication: In vitro antibacterial activity of essential oils from twelve aromatic plants from East Kalimantan, Indonesia. Biodiversitas 20: 2039-2042. In the aim of this works was to investigate the antibacterial activity of twelve essential oils against Streptococcus mutans and Streptococcus sobrinus, oral pathogen causing dental caries. The essential oils were collected by a steam distillation method. Refractive index was measured by using a refractometer. The antibacterial activity of essential oils was determined using an agar well diffusion method. The yields of essential oils varied with the plant species. The steam distillation yielded clear to yellowish essential oils. Refractive indexes of oil were found to be in the range of 1.344 to 1.500. Syzigium sp. appeared to be more abundant in oil (1.54%) than the other plant species, while C. odorata was poorer (0.04%). All of the essential oils tested showed a varied level of inhibition zone (0-53.65 mm) against S. mutans and S. sobrinus. The oil from leaves of Cymbopogon citratus had the highest activity against S. sobrinus and S. mutans (53.15 and 52.85 mm, respectively). On the other hand, the Magnolia x alba oil showed the lowest activity against S. mutans and S. sobrinus (10.50 and 11.65 mm, respectively). The research results demonstrated that the essential oil in this study has the potency for development of dental health products for preventing and treating oral infections.